URGENSI PERTIMBANGAN MAHKAMAH AGUNG DALAM HAL PEMBERIAN GRASI SEBAGAI HAK PREROGATIF PRESIDEN - , VERONICA DYASTI ARUM S, Sardjuki, S.H., M.H. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Clemency is a right held by the President as stated in Article 14 paragraph (1) of 1945 Constitution of the Republic of Indonesia (RI 1945). Consideration of the Supreme Court indicate restrictions in granting clemency powers of the President. Granting presidential pardons are granted authority by the Constitution - Constitution of 1945 of the Republic of Indonesia. Setting clemency shall be regulated by Act - Act No. 22 of 2002 on clemency , as amended by Act - Act No. 5 of 2010 on Amendment - Law No. 22 Year 2002 on clemency. Supreme Court the authority to examine and decide on the final level. Closely related to the function of the judiciary is to the right of judicial review, which is authorized to test / assess the substantive legislation under the Act about whether a rule in terms of its content (the material)., Substance laws regulate the process of granting clemency without consideration relating to criminal justice system (criminal justice system) itself. However, after 2002 the granting of pardon is based on Law No. 22 Year 2002 on Clemency (Clemency Act). This research is a normative juridical documentation methods appropriate bibliography of secondary data, ie by collecting data, reviewing legal theories relating to research problems, reviewing the applicable laws and regulations, and analyzing research data. Research carried out to find out about the urgency of the Supreme Court judgment against the prerogative of granting pardon as president. Granting clemency was indeed face there is no problem because the full prerogative of the president. However, the urgency of the Supreme Court who is legally authorized parties consulted, strongly suggested would not convicted or granted clemency. Given the crimes they have committed such a crime types ekstraordinaryHigh-class crime, and endangering the lives of the future generation.